Le crime du comte Neville d’Amélie Nothomb ou le roman familial d’une névrosée - Hastings, Valerie (Romanica Silesiana)
The Crime of Count Neville is primarily a story of a complex father–daughter relationship, culminating in the attempted murder of the count’s daughter by her own father. Infanticide is inevitable for Sérieuse, which parallels the mythological story of Iphigenia. But Nothomb also develops on an extra-diegetic level, as the meta-narrative of the genesis of the Freudian Family Romance or the Novel itself. Between the concepts of “bastard” and “foundling,” this novel contains many autobiographical elements and borrows from other literary works, most noticeably from Oscar Wilde’s collection Lord Arthur Savile’s Crime.